Case report: Severe respiratory failure caused by licorice - Taniguchi, Hiroaki; Terayama, Takero; Kiriu, Nobuaki; Kato, Hiroshi; Seno, Soichiro; Sekine, Yasumasa; Tanaka, Yoshihiro; Kiyozumi, Tetsuro (Frontiers in Pharmacology, 2023)
Licorice, one of the most commonly used herbs, can cause hypokalemia, metabolic alkalosis, and apparent mineralocorticoid excess, also known as pseudoaldosteronism. Herein, we present a case of diaphragmatic dysfunction caused by licorice administration. An 80-year-old woman who had been taking dietary supplements and following a restricted diet for approximately 6 months was brought to the emergency department with impaired consciousness. Chronic respiratory acidosis was observed, and hypertension and hypokalemia became more prominent during hospitalization. History revealed that she was taking herbal medicines containing licorice. Based on the results of hormone tests, the patient was diagnosed with pseudoaldosteronism. Chest radiography and pulmonary function tests confirmed the clinical diagnosis of diaphragmatic dysfunction. The metabolic alkalosis resulting from licorice administration may have contributed to the impairment of the respiratory muscles. This case suggests that caution should be exercised when using licorice in patients with preexisting health or medical issues such as advanced age, malnutrition, and electrolyte imbalance.